Delusion and Delirium in Neurodegenerative Disorders: An Overlooked Relationship? - Urso, Daniele; Gnoni, Valentina; Filardi, Marco; Logroscino, Giancarlo (Frontiers in Psychiatry, 2022)
Delusions are part of the neuropsychiatric symptoms that patients suffering from neurodegenerative conditions frequently develop at some point of the disease course and are associated with an increased risk of cognitive and functional decline. Delirium is a syndrome characterized by acute onset of deficits in attention, awareness, and cognition that fluctuate in severity over a short time period. Delusions and delirium are frequently observed in the context of neurodegeneration, and their presence can easily mislead clinicians towards a misdiagnosis of psychiatric disorder further delaying the proper treatment. Risk factors for developing delusion and delirium in neurodegenerative conditions have been investigated separately while the possible interplay between these two conditions has not been explored so far. With this study, we aim to achieve a more comprehensive picture of the relationship between delusions and delirium in neurodegeneration by analysing prevalence and subtypes of delusions in different neurodegenerative disorders; providing an overview of clinical tools to assess delusions in neurodegenerative patients and how delusions are covered by delirium assessment tools and discussing the possible common pathophysiology mechanisms between delusion and delirium in neurodegenerative patients. A more extensive characterization of the relationship between delusions and delirium may help to understand whether delusions may constitute a risk factor for delirium and may ameliorate the management of both conditions in patients with neurodegenerative disorders.